2010
DOI: 10.1002/etc.181
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the environmental fate of perfluorooctanoic acid and perfluorooctanoate: An investigation of the role of individual species partitioning

Abstract: A multimedia multi-species environmental fate model was developed for the conjugate pair perfluorooctanoic acid (PFOA):perfluorooctanoate (PFO). The model allows assessment of the relative contribution of each individual species, in equilibrium with each other, to the overall environmental movement of the pair. The Lake Ontario (Canada/USA) watershed system was selected for this investigation and is simulated in a single-region, seven-compartment model, including a water surface microlayer, and aqueous aerosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 55 publications
(121 reference statements)
4
34
0
Order By: Relevance
“…For some PFAAs, especially the strongly acidic PFSAs, the neutral form represents only a small fraction of all molecules at pH values typical in the environment, and likely does not play a major role in controlling environmental behaviour. In contrast, for PFCAs it has been suggested that the neutral form may be relevant in environmental transport and partitioning processes [18] as well as in bioaccumulation. [33] In addition, COSMOtherm estimates made here represent only the properties of PFAS monomers.…”
Section: Limitations Of Property Estimationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For some PFAAs, especially the strongly acidic PFSAs, the neutral form represents only a small fraction of all molecules at pH values typical in the environment, and likely does not play a major role in controlling environmental behaviour. In contrast, for PFCAs it has been suggested that the neutral form may be relevant in environmental transport and partitioning processes [18] as well as in bioaccumulation. [33] In addition, COSMOtherm estimates made here represent only the properties of PFAS monomers.…”
Section: Limitations Of Property Estimationsmentioning
confidence: 99%
“…However, recent studies have shown that PFASs can also adsorb to interfaces as previously discussed and that these adsorption properties could have a strong influence on the environmental distribution of PFASs. [18] Goss has tested the possibility using COSMOtherm to predict adsorption constants for the air-water interface for a set of more than 200 organic compounds [57] that included some FTOHs and fluorotelomer olefins. Moreover, Arp and Goss have developed a COSMOthermbased model to predict the partitioning behaviour at the gasparticle interface and evaluated it with some measurement for C 6 -C 8 PFCAs.…”
Section: Limitations and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the relative importance of each species and its related processes should become apparent through application of the models. Multimedia fate models that rely on these standard equilibrium equations have already been used but without directly addressing the question of their applicability [20][21][22][23][24][25][26]. The apparent success of the equilibria equations in the multimedia models may have been due to a masking effect from the multimedia model complexity.…”
Section: Introductionmentioning
confidence: 97%
“…However, the common used wastewater treatment plant (WWTP) can not achieve the complete removal of pollutants, thus appearing the point sources of water pollution (Pham and Proulx, 1997). Also, WWTPs can become the atmospheric sources of some organic pollutants, such as volatile organic compounds (Simonich et al, 2000;Escalasa et al, 2003;Wu et al, 2006), perfluorooctanoic acid (Webster et al, 2010), polyfluoroalkyl compounds (Ahrens et al, 2011) and PAHs (Byrns, 2001;Seth et al, 2008). Recently, intense attention has been paid on PAHs in the atmosphere (Simcik et al, 1999;Park et al, 2002;Omar et al, 2006;Zhang et al, 2011a), as the most carcinogenic, mutagenic and toxic contaminants (Deng et al, 2006).…”
Section: Introductionmentioning
confidence: 99%